Comparative outcome analyses of differently surgical approaches to lumbar disc herniation - Lakičević, Goran (Array, 2009)
Summary: Lumbar disc herniations (LDH) occur in the lower back, most often between the fourth and fifth lumbar vertebral bodies or between the fifth and the sacrum. It is evident lack of studies dealing with comparative analysis of the surgical outcomes of the spine operation techniques. In this paper we analyzed and compared outcomes of the LDH standard techniques (laminectomy and hemilaminectomy), and contemporary operation techniques (interlaminectomy, and microdiscectomy). Adult patients (18–75 years of age) surgically treated on the Neurosurgery Department of the University Clinical Hospital Mostar – Bosnia and Herzegovina between January 1998 and December 2007 were sampled as subjects. We analyzed and compared, number of the LDH surgically treated patients; age, patient’s satisfaction with postoperative status, postoperative recurrence of the LDH; incidence of the postoperative complications, and duration of hospitalization. In conclusion, modern operating methods have to be considered as superior over traditional operating types mostly because of smaller violations of forms and integrity of lumbar spine